2019
DOI: 10.1111/tbed.13146
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for enhanced surveillance of foot‐and‐mouth disease in endemic settings using milk samples

Abstract: Summary Under‐reporting of foot‐and‐mouth disease ( FMD ) masks the true prevalence in parts of the world where the disease is endemic. Laboratory testing for the detection of FMD virus ( FMDV ) is usually reliant upon the collection of vesicular epithelium and fluid samples that can only be collected from acutely infected animals, and therefore animals with sub‐clinical infection may not be identified. Milk is a non‐invasive sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…Previous studies have demonstrated the potential of using milk from individual animals as an alternative sample type for FMDV detection and surveillance (Armson et al, 2019) and that it is possible to detect FMDV in highly diluted milk samples from individual clinical cases (Armson et al, 2018). This pilot study aimed to expand on this work and explore the use of pooled milk as a cost-effective, non-invasive alternative sample matrix for the surveillance of FMD by comparing the household-level incidence of clinical disease to FMDV RNA detection by rRT-PCR from pooled milk facilities in an endemic region of Kenya.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated the potential of using milk from individual animals as an alternative sample type for FMDV detection and surveillance (Armson et al, 2019) and that it is possible to detect FMDV in highly diluted milk samples from individual clinical cases (Armson et al, 2018). This pilot study aimed to expand on this work and explore the use of pooled milk as a cost-effective, non-invasive alternative sample matrix for the surveillance of FMD by comparing the household-level incidence of clinical disease to FMDV RNA detection by rRT-PCR from pooled milk facilities in an endemic region of Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the mammary gland is highly susceptible to FMDV replication (Burrows, Mann, Greig, Chapman, & Goodridg, ) and that FMDV can be detected by real‐time reverse transcription polymerase chain reaction (rRT‐PCR) assays in milk from experimentally infected cattle, before and during the appearance of clinical signs, and up to 28 days post‐infection (Armson et al, ; Reid et al, ). FMDV RNA has also been detected in milk samples from naturally infected cattle (Armson et al, ; Ranjan et al, ; Saeed et al, ) and buffaloes (Ahmed et al, ) in endemic settings. Furthermore, using individual milk samples collected from naturally infected cattle in northern Tanzania, it has been demonstrated that VP1 sequences could be obtained, corresponding with those generated from clinical samples collected from lesions from the same animal (Armson et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Goller et al ( 18 ) explored milk as a non-invasive sample for FMDV surveillance using RT-qPCR. They demonstrated that the RT-qPCR on milk sample was capable of detecting FMDV RNA 18 days after contact, which is later than the viral RNA detected in serum samples, suggesting milk as a feasible sample for FMD surveillance ( 18 , 21 ). In addition, EDTA-treated blood samples have also been explored as a source of the viral RNA for the diagnosis of FMDV using RT-qPCR, owing to the samples' stability during transportation, as well as the ease of sample processing at the diagnostic laboratory ( 41 ).…”
Section: Nucleic Acid Detection Methodsmentioning
confidence: 99%
“…Despite limited reports on foodborne viruses in milk products, there is evidence that points to likely viral contamination of milk products in some SSA. For example, foot-and-mouth disease virus (FMDV), a pathogen to cloven-hoofed animals, was recently detected in cow milk samples collected during the FMD outbreak in Tanzania (Armson et al, 2019). In the study of Armson et al (2019), 73/190 (38%) of the milk samples were contaminated with the RNA of FMDV.…”
Section: Milkborne Viral Pathogensmentioning
confidence: 99%